Good night, Gorilla - Rathmann, Peggy (New York : Putnam, 1994)
An unobservant zookeeper is followed home by all the animals he thinks he has left behind in the zoo.
Cover title.
On board pages.
Keywords: Bedtime -- Fiction; Board books; Zoo animals -- Fiction; Zoos -- Fiction; Bedtime -- Fiction; Zoo animals -- Fiction; Zoos -- Fiction